The Effect of Participatory Teaching of Positive Thinking Skills on Nurses Communication Skills in the Emergency Department of a Teaching Hospital - Shayesteh Salehi; Fatemeh Hashemi; nosrat Avaznejad; Fatemeh Karami (Kerman University of Medical Sciences, 2018)
The Effect of Participatory Teaching of Positive Thinking Skills on Nurses Communication Skills in the Emergency Department of a Teaching Hospital   Salehi Shayesteh1, Hashemi Fatemeh2*, Avaznejad Nosrat3, Karami Robati Fatemeh4 1. Associate Professor, Community Health Research Center, Islamic Azad University, Isfahan Branch (Khorasgan), Isfahan, Iran 2. MSc, Afzalipour Hospital, Kerman University of Medical Sciences, Kerman, Iran 3. MSc, Kerman University of Medical Sciences, Kerman, Iran 4. MSc, Clinical Research Unit, Afzalipour Hospital, Kerman University of Medical Sciences, Kerman, Iran *Correspondence: Imam Khomeini Highway, next to Shahid Bahonar University, Afzalipour Hospital Tel: 0983431328000                             Email: fa.hashemi299@yahoo.com Abstract: Background & Objectives: Correct relationship between nurses and patients will improve the therapeutic outcomes and improve the patient's recovery process. One of the most important items in improving communication skills, as an essential part of providing nursing services, is the attitude and feedback of nurse to various phenomena and to create the necessary internal preparation for making positive changes in cognitive domain. This study aimed to investigate the effect of participatory teaching of positive thinking skills on communication skills of nurses in the emergency department of a selected hospital in Kerman city. Methods: This analytical study was an interventional study and it was conducted on 60 nurses at the selected educational hospital divided into the two groups of experimental and Control. Queendom Communication Skills Questionnaire was used for data collection. The experimental group received positive thinking skills education during 9 sessions. Independent t-test, ANOVA and single-variable covariance analysis test were used for data analysis. Data were entered into SPSS version 22. Results: Mean of total score of communication skills increased in the experimental group. Based on the post-test results, there was a significant improvement in the mean scores of listening skills, the ability to receive and send messages, emotional control, connection with decisiveness and insight into the communication process of nurses  based on their group (P <0.05). Conclusion: Considering the effectiveness of teaching positive thinking skills in increasing nurses' communication skills, it is recommended to provide training for these skills from the beginning of nursing students' education.   Keywords: Participatory Education, Positive Thinking Skills, Communication Skills, Nurses, Emergency Department, Teaching Hospital     Citation: Salehi S, Hashemi F, Avaznejad N, Karami Robati F. The Effect of Participatory Teaching of Positive Thinking Skills on Nurses Communication Skills in the Emergency Department of a Teaching Hospital. Journal of Health Based Research 2018; 4(1): 63-76.